Microencapsulated phase change materials with graphene-based materials: Fabrication, characterisation and prospects. (October 2022) - Su, Weiguang; Hu, Meiyong; Wang, Li; Kokogiannakis, Georgios; Chen, Jun; Gao, Liying; Li, Anqing; Xu, Chonghai
Abstract: Microencapsulated phase change material (MEPCM) is an efficient thermal energy storage material. However, the heat charging/discharging rate of MEPCMs is limited by their low thermal conductivity. Graphene-based materials (i.e. graphene, graphene oxide (GO), reduced graphene oxide (rGO)) have ultrahigh thermal conductivity and have been used as thermal conductive enhancement materials in MEPCMs. This paper reviewed the preparation and characterisation methods of graphene-based materials for MEPCMs. The in-situ polymerization method is the most widely adopted for the preparation of graphene-based microcapsules, and GO-enhanced MEPCM could generate the best morphology result. By embedding graphene in organic shell hybrid structure, the thermal conductivity of microcapsules was increased to as high as 7.2 W/(m∙K). The addition of graphene significantly reduced the supercooling and more than 90% of the leakage rate of MEPCM. It also effectively improved the mechanical strength and photothermal conversion efficiency of MEPCM. In addition, GO exhibits amphiphilicity and can be used as an emulsifier for the preparation of Pickering emulsions. Its amphiphilic properties can be adjusted by: mixing GO with other emulsifiers, altering its pH value, surface modification, and fabricating Janus GO. Graphene can also be used in the preparation of Pickering emulsions after surface modification. Graphene quantum dots (GQDs) is used as a zero-dimensional surfactant due to their oxygen-containing functional groups, which exhibit good amphiphilic properties. In summary, it is beneficial to modify graphene-based materials as surfactants to replace conventional surfactants during the preparation of oil-water emulsions and high-quality MEPCMs. Highlights: In-situ polymerization method is commonly used for the preparation of graphene-based microcapsules. The thermal conductivity of microcapsules reached 7.2 W/(m∙K) by graphene hybrid shell. Integrated graphene into MEPCM significantly reduced the supercooling and leakage rate. GO amphiphilic properties can be adjusted by mixing with other emulsifiers, altering the pH value, surface modification, and fabricating Janus GO. Modified graphene-based materials as surfactants can be used for MEPCM preparation.